1982
DOI: 10.1073/pnas.79.5.1466
|View full text |Cite
|
Sign up to set email alerts
|

Use of different tRNASer isoacceptor species in vitro to discriminate between the expression of plasmid genes.

Abstract: A simplified translation system coupled to DNA transcription that involves assaying the synthesis of the first dipeptide of a gene product has been described recently Procx NatL Acad. Sci USA 78,[4261][4262][4263][4264]. Using this dipeptide system, we have investigated the expression ofgenes carried on plasmids coding for (8-lactamase, ribosomal protein L12, and the chloroplast large subunit (LS) of ribulosebisphosphate carboxylase (RbuBPCase). Although all three nascent gene products begin with the sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…A limited in vitro translation reaction in which only the first two tRNAs are present was performed, using malEA2-8 and malEA2-8supl mRNAs as substrates. The rate of synthesis of the 2-amino-acid initiation peptide fMetIle was then determined as previously described (9,24,30) (Table 2). Results from this analysis revealed that the rate of translation of the initiation peptide from malEA2-8supl mRNA was approximately 18 times higher than from malEA2-8 mRNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited in vitro translation reaction in which only the first two tRNAs are present was performed, using malEA2-8 and malEA2-8supl mRNAs as substrates. The rate of synthesis of the 2-amino-acid initiation peptide fMetIle was then determined as previously described (9,24,30) (Table 2). Results from this analysis revealed that the rate of translation of the initiation peptide from malEA2-8supl mRNA was approximately 18 times higher than from malEA2-8 mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro transcription of the malE gene was carried out as described previously (32). In vitro translation and quantitation of the rate of synthesis of the 2-amino-acid initiation peptide Met-Ile from malEA2-8 and malEA2-8supl mRNAs was performed essentially as described by Weissbach and coworkers (9,24,30). The isolation of 70S initiation complexes was carried out as described previously (29).…”
Section: Methodsmentioning
confidence: 99%
“…An identical procedure was followed for constructing the recombinant plasmids pBC303.480 and pBC303.481, except that gene fusion was achieved in a different translational phasing. translation coupled system (6). In this system, plasmiddirected protein synthesis is limited to the formation of the N-terminal dipeptide of the gene product instead of the completed protein.…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory has recently developed a procedure for investigation of prokaryotic gene expression in an in vitro DNA-directed system by measuring the synthesis of the first di-or tripeptide characteristic of the gene product (1)(2)(3)(4)(5). For example, using the recombinant plasmid pNF1337, which contains the genes for Escherichia coli ribosomal proteins L10 and L12 and the (3 subunit of RNA polymerase, we studied the expression of these three genes in a coupled in vitro system by measuring the formation of fMet-Ala, fMet-Ser, and fMet-Val, respectively (1,2,5).…”
mentioning
confidence: 99%
“…For example, using the recombinant plasmid pNF1337, which contains the genes for Escherichia coli ribosomal proteins L10 and L12 and the (3 subunit of RNA polymerase, we studied the expression of these three genes in a coupled in vitro system by measuring the formation of fMet-Ala, fMet-Ser, and fMet-Val, respectively (1,2,5). The advantage of this system was that a specific di-or tripeptide product could be measured sensitively by thinlayer chromatography (1,2) or by a rapid extraction procedure (4,5). In addition, the system only contained five purified protein factors and also could be used to quantitate the amount of active mRNA present (3).…”
mentioning
confidence: 99%